Effect of Pollen Feed on Parasitization and Predatism of Cephalonomia stephanoderis onHypothenemus hampei - Dwi Suci Rahayu; Endang Sulistyowati (Indonesian Coffee and Cocoa Research Institute, 2014)
Biological control of the coffee berry borer (Hypothenemus hampei)using parasitoid Cephalonomia stephanoderishas been developed through the improvement of the parasitoid role may using pollens as feed source. The objective of this study was to investigate the effect of cover crop and weed pollens on parasitization and predatism of C. stephanoderis.The applied treatments were pollens of Turnera ulmifolia, Arachis pintoi, Ageratum conyzoidesadded in glass tube that consist of 10 CBB pupaes and a mated female of C. stephanoderis. Number of pupae parasitized and pupae preyed were observed. The result showed that addition of A. Pintoi pollen increased the number of pupae parasitized at 135% whereas addition of T. ulmifolia and A. conyzoides pollens did not affect parasitization of C. Stephanoderis. The predatismof C. stephanoderiswas higher than parasitization to pupae of H. hampei which showed that the behavior of C. stephanoderiswas parasitization. Addition of T. ulmifolia, A. pintoi, and A. conyzoidespollens increased the number of pupae predatism at 132%, 102%, and 225%, respectively. Key words: Ageratum conyzoides, Arachis pintoi, Cephalonomia stephanoderis, Hypothenemus hampei,parasitization, predatism, pollens, Turnera ulmifolia